A Review Paper on Biological Population (International Journal of Innovative Research in Computer Science & Technology, 2022)
It is debatable if population increase and  economic growth are linked. This article uses historical  statistics to show how people growth, per person  production growth, and overall economic growth have all  correlated during the last 200 years. Low growing  populations in rising countries is expected to produce societal and economic problems, while fast demographic  development in low-income countries is expected to hinder  development. Several individuals are opposed to foreign  immigration that might help to alleviate these inequalities.  Reduced populations explosion and restricted immigration,  so based income imbalance evaluations, may contribute to  higher factors such as economical imbalance. The ideas of  broad, goal, and sample frame are described in this article  in response to errors and disputes surrounding them, as well  as the fact that the links between them have never been  explained in the context of a formal research. Based on a  general situation, these principles are explored in this  paper. In a qualitative study with a big study population,  we generally try to explain why it is important to identify  the general, target, and accessible audiences. In qualitative  research, the study shows how the research objective,  settings, and assumptions may influence the contents and  intensity of the target and accessible population.
Keywords: Biological; Economy; Extinction; Population; Species